Abstracts : 31 st European Congress of Pathology. (Virchows Archiv: European Journal of Pathology)
B Results: b Multivariate logistic regression analysis showed that tumours located in the upper oesophagus (OR=2.93, 95%CI,1.02-8.42), large tumour circumferential extension (OR=5.39, 95%CI,1.06-27.47), advanced tumour invasion depth (OR=4.12, 95%CI,1.81-9.33) and numerous Lugol-voiding lesions in background mucosa (OR=2.65, 95%CI,1.10-6.37) were risk factors for DI. B Background & Objectives: b We employed two methods for the detection of HER2 genetic heterogeneity (GH; a mixture of classic HER2 positive and negative tumour cells) and non-GH (NGH; a mixture of classic HER2 positive tumour cells and HER2 gene amplified tumour cells without HER2 protein): 1) visual microscopic HER2-intratumoural heterogeneity (ITH) and 2) quantitative HER2-diversity (based on enumeration of large numbers of individual cells in respect to HER2 gene copy number and protein expression levels) in relation to neoadjuvant trastuzumab-based chemotherapy. B Results: b Four mPTC groups based on size and distance from the thyroid capsule were identified: Group A, subcapsular tumour <5 mm; Group B, capsular tumour (i.e. a tumour reaching the thyroid capsule) <5 mm; Group C, subcapsular tumour U > u 5 mm; Group D, capsular tumour U > u 5 mm. Multivariate analysis correlated Group D tumours with (i) microscopic features: presence of psammoma bodies within the tumour, tall cell features, tumour fibrosis, with an inverse correlation to follicular growth pattern; (ii) characteristics of tumour growth: infiltrative border, unicentric tumour with intraglandular tumour spread, vascular invasion, psammoma bodies in the parenchyma surrounding the tumour; (iii) clinicopathologic features: tall cell or classic papillary carcinoma diagnoses, I BRAF i V600E mutation, lymph node metastases, ATA risk group, with an inverse correlation to nodular hyperplasia, to the presence other thyroid neoplasms, to a diagnosis of Papillary microtumour or to that of NIFTP.